Tax Evasion and Violations Perspektive Blibiometrics Analysis - Prasetiyo, Yudhi; Riyani, Etik Ipda; Novita Nugraheni (Jurnal Ekonomi, 2024)
The research is a form of descriptive qualitative research with the aim of examining a comprehensive, exploratory study regarding tax evasion as a frequently occurring phenomenon carried out by taxpayers in implementing tax provisions. The sample consists of 1000 documents contained in the crossref database in the period 2014-2024 with the keyword tax evasion. This research uses the bliobiometric analysis method with the help of VosViewer to analyze the research results based on visualization mapping. Based on the results computed by clustering via VosViewer, there are seven clusters in this research which are distributed in several colors, namely cluster 1 is marked in red, cluster 2 is green, cluster 3 is blue, cluster 4 is yellow, cluster 5 is purple, cluster 6 is blue. young and cluster 7 are colored orange, where the distribution of data can be seen in network visualization.